PERANCANGAN SISTEM INFORMASI E-PSIKOTES MENGGUNAKAN PHP DAN MYSQL DI PT. INFOMEDIA HUMANIKA BANDUNG - Roni Surahman (INFOKOM (Informatika & Komputer), 2018)
This study aims to analyze, design and build psychotes information systems at PTInfomedia Humanika Bandung so that the process of taking data psychotes can be faster,accurate and efficient.Data collection methods was using observation, intervie andliterature study, while the method of this information system design was using objectorientedapproach with UML modeling (Unified Modeling Language).Softwaredevelopment method using prototype method, whichis implemented with PHPprogramming language and MySQL as database.The main problem is the length of the scanning process due to the large numberof data and inconsistencies in the procedure of charging test answers, the inefficiency inrecording the data because it must be input into Microsoft Excel application. Toovercome these problems then made e-psychotes information system with software testingmethods blackbox method.The suggestions given is: Performing system maintenance regularly, doing systemdevelopment, Held training for User and Admin about system usage procedure.